2019
DOI: 10.1111/sms.13422
|View full text |Cite
|
Sign up to set email alerts
|

The role of resilience in student‐athletes' sport and school burnout and dropout: A longitudinal person‐oriented study

Abstract: Although it has been shown that student‐athletes who pursue upper secondary school alongside with an athletic career may be prone to sport and school burnout, the concrete life changes resulting from burning out, such as dropping out of sport or school, have not been investigated. Moreover, it is unknown why some student‐athletes do not burnout. The purpose of the present study was to examine whether there are different kinds of profiles—based on the level and development of sport and school burnout symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
2
37
0
3
Order By: Relevance
“…Furthermore, findings from longitudinal studies have consistently supported the association between high school burnout and emotional issues, such as depression and anxiety symptoms [33,34]. In a similar vein, previous research has also found that students with a low level of school-related emotional exhaustion are more resilient and able to 'bounce back' from negative experiences [35,36].…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, findings from longitudinal studies have consistently supported the association between high school burnout and emotional issues, such as depression and anxiety symptoms [33,34]. In a similar vein, previous research has also found that students with a low level of school-related emotional exhaustion are more resilient and able to 'bounce back' from negative experiences [35,36].…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, the role of identity development in dropping out from sports and school has not STUDENT-ATHLETES' IDENTITY PROFILES 10 been examined although it can be assumed that student-athletes who have a strong identity in one domain (e.g., sports) may be more likely to drop out from the other domain (e.g., school) than student-athletes with a balanced identity. A recent longitudinal study in Finland showed that burned-out student-athletes were more likely to quit sports than school (Sorkkila, Tolvanen, Aunola, & Ryba, 2019). However, it is unknown how their identity was formed and whether, for example, the dropped-out student-athletes were particularly self-identified as students.…”
Section: The Role Of Identity Development In Sports and School Achievements And Dropoutmentioning
confidence: 99%
“…Although there is a lack of literature on strategic learning skills associated with sport drop-out, we found some agreement with evidence on similar skills and maladaptive sport processes (burnout profiles) that allow us to frame a reference theory. Burnout profiles have been defined as a state of sport/school exhaustion related to chronic stress and have been studied in sport and at school jointly [ 55 ]. This burnout process involves a lack/insufficient level of skills that are common to the two areas (sport and school), similar to the strategic learning skills, objects of the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence comes into play in a phenomenon such as burnout in sport that has commonalities with the drop-out from sport investigated here. A stronger risk of sport drop-out is related to a low level of resilience-related skills [ 55 ], high level of anxiety [ 25 ] and low perception of competence [ 24 ]. The critical level of these competences reported in the literature may represent a risk factor comparable to the critical value of affective–motivational strategic learning skills that emerged in our study.…”
Section: Discussionmentioning
confidence: 99%